2021
DOI: 10.1155/2021/5512961
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Investigations of Extracts of Zanthoxylum rhetsa

Abstract: Zanthoxylum rhetsa has been consumed in the diet in northern Thailand and also used as a medicament in ancient scripture for arthropathies. Thus, this study aimed to evaluate the activity of various extracts from differential parts of Z. rhetsa via inhibition of inflammatory mediators (NO, TNF-α, and PGE2) in RAW264.7 macrophages. The chemical composition in active extracts was also analyzed by GC/MS. The parts of this plant studied were whole fruits (F), pericarp (P), and seed (O). The methods of extraction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A study by Su et al on various metabolites secreted from different organs of the Acanthopanax senticosus plant, showed that of 130 metabolites, 39 metabolites were expressed in roots, 51 metabolites were expressed in seeds, and 40 metabolites were expressed in leaves [ 24 ]. A similar study by Imphat et al reported on the investigation of Z. rhetsa for anti-inflammatory effects; it showed that the extraction of Z. rhetsa pericarp resulted in a higher total yield of extract than the fruit and seed parts, from four different type of extraction, including hexane, ethanol (50% and 90%), decoction, and water extraction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study by Su et al on various metabolites secreted from different organs of the Acanthopanax senticosus plant, showed that of 130 metabolites, 39 metabolites were expressed in roots, 51 metabolites were expressed in seeds, and 40 metabolites were expressed in leaves [ 24 ]. A similar study by Imphat et al reported on the investigation of Z. rhetsa for anti-inflammatory effects; it showed that the extraction of Z. rhetsa pericarp resulted in a higher total yield of extract than the fruit and seed parts, from four different type of extraction, including hexane, ethanol (50% and 90%), decoction, and water extraction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than the plant part, the usage of solvent also determines the total extraction yield. Several studies showed that ethanol extraction offered the highest total yield for Zanthoxylum plant maceration [ 15 , 22 ]. Essential oil is known as a non-polar compound that consists of ether, keton, aldehyde, and terpenoid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations